Algal characterization and bioaccumulation of trace elements from polluted water - Sahu, Y.K.; Patel, K.S.; Martín Ramos, P.; Rudzińska, M.; Górnaś, P.; Towett, Erick K.; Martín Gil, J.; Tarkowska-Kukuryk, M. (Springer, 2020)
Algae are a group of autotropic and eukaryotic organisms that play a significant role in the food, pharmaceutical, cosmetic, fuel, and textile industries. They are an important part of our ecosystem, and they can help control the growing problem of pollution. In this work, the carotenoid, sterol, polyphenol and mineral content, spectral and thermal characteristics of six common river algae, viz. Chara spp., Hydrodictyon spp., Lyngbya spp., Nitella spp., Pithophora spp., and Spirogyra spp., collected from Kharun river (India), were evaluated. The concentration of oil, total polyphenols, flavonoids, and mineral ranged from 0.4 to 4.3%, from 2705 to 4450 mg/kg, from 1590 to 2970 mg/kg, and from 85,466 to 122,871 mg/kg of algae (dw), respectively. The concentration of carotenoids and sterols varied from 1.6 to 109 mg/kg and from 522 to 35,664 mg/kg. The potentiality towards the bioaccumulation of 22 trace elements from the surface reservoir was assessed and discussed in relation to carbonate inlay of the algae wall and to the ions ability to bind to pectin, polypeptides, carotenoids, polyphenols, and flavonoids, on the basis of infrared spectroscopy data. In view of the extremely high enrichment factors found for certain elements, such as P, Co, Cu, Pb, and Fe, some of these algae hold promise as bioindicators for the detection of these elements in aquatic environments. Ordination analysis was used to measure the variance gradient of the algal data.